Blood–Brain Barrier Dysfunction in a 3D In Vitro Model of Alzheimer's Disease. Issue 20 (12th August 2019) - Shin, Yoojin; Choi, Se Hoon; Kim, Eunhee; Bylykbashi, Enjana; Kim, Jeong Ah; Chung, Seok; Kim, Doo Yeon; Kamm, Roger D.; Tanzi, Rudolph E.
Abstract: Harmful materials in the blood are prevented from entering the healthy brain by a highly selective blood–brain barrier (BBB), and impairment of barrier function has been associated with a variety of neurological diseases. In Alzheimer's disease (AD), BBB breakdown has been shown to occur even before cognitive decline and brain pathology. To investigate the role of the cerebral vasculature in AD, a physiologically relevant 3D human neural cell culture microfluidic model is developed having a brain endothelial cell monolayer with a BBB‐like phenotype. This model is shown to recapitulate several key aspects of BBB dysfunction observed in AD patients: increased BBB permeability, decreased expression of claudin‐1, claudin‐5, and VE‐cadherin, increased expression of matrix‐metalloproteinase‐2 and reactive oxygen species, and deposition of β‐amyloid (Aβ) peptides at the vascular endothelium. Thus, it provides a well‐controlled platform for investigating BBB function as well as for screening of new drugs that need to pass the BBB to gain access to neural tissues. Abstract : An increase in permeability of the blood–brain barrier (BBB) has long been considered a key factor in the cause and consequences of Alzheimer's disease (AD). In this study, a physiologically relevant 3D model is developed and used to investigate several key aspects of BBB dysfunction in AD and to provide a standardized platform for screening of new drugs.